2021
DOI: 10.3390/ijms22179447
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfonamide-Based Carbamates as Selective Inhibitors of BChE

Abstract: A series of 14 target benzyl [2-(arylsulfamoyl)-1-substituted-ethyl]carbamates was prepared by multi-step synthesis and characterized. All the final compounds were tested for their ability to inhibit acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) in vitro, and the selectivity index (SI) was determined. Except for three compounds, all compounds showed strong preferential inhibition of BChE, and nine compounds were even more active than the clinically used rivastigmine. Benzyl {(2S)-1-[(2-methoxybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 94 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…The selective index for BChE (SI (AChE/BChE) ) was 3.76 and 3.46 for MYR-PVP 1:8 w / w and 1:9 w / w respectively). The selectivity of MYR can be attributed to differences in the active sites of AChE and BChE enzymes [ 94 , 95 ]. BChE has a larger and more flexible active site compared to AChE, allowing for a wider range of interactions with inhibitors such as MYR.…”
Section: Resultsmentioning
confidence: 99%
“…The selective index for BChE (SI (AChE/BChE) ) was 3.76 and 3.46 for MYR-PVP 1:8 w / w and 1:9 w / w respectively). The selectivity of MYR can be attributed to differences in the active sites of AChE and BChE enzymes [ 94 , 95 ]. BChE has a larger and more flexible active site compared to AChE, allowing for a wider range of interactions with inhibitors such as MYR.…”
Section: Resultsmentioning
confidence: 99%
“…(2021) performed 20 ns MD simulations of the uncleaved tcAChE-rivastigmine complex in triplicates using Amber16 software. Despite studying a different organism, Magar et al 82 also observed that rivastigmine is deeply buried inside the active-site gorge of AChE, interacting with the catalytic triad and nearby residues throughout the simulations. 82 Distinct interactions with rivastigmine were observed between the docking solution (Figure 3) and the representative structure of wild type hAChE (Figure 5).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Despite studying a different organism, Magar et al 82 also observed that rivastigmine is deeply buried inside the active-site gorge of AChE, interacting with the catalytic triad and nearby residues throughout the simulations. 82 Distinct interactions with rivastigmine were observed between the docking solution (Figure 3) and the representative structure of wild type hAChE (Figure 5). This difference may occur since docking algorithms assign some approximations such as rigid receptors, which can affect final predictions.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Our group has previously reported several studies using this approach for different types of L–R complexes from different biological systems. 24–29 Recently, we reported a study showing the possibilities and limitations of this approach. 30…”
Section: Introductionmentioning
confidence: 99%